Sexualized drug injection among men who have sex with men in Madrid and Barcelona as the first episode of drug injecting - Juan-Miguel Guerras; Patricia García de Olalla; María José Belza; Luis de la Fuente; David Palma; Jorge del Romero; Jorge-Néstor; Juan Hoyos; the Methysos Project Group (BMC, 2021)
Abstract Background We estimate the prevalence of drug injection, the variables associated with having ever injected and the proportion of ever injectors whose first drug injection was for having sex; we describe the first drug injection episode, analyze the drugs most frequently injected and estimate the prevalence of risky injecting behaviors. Methods The participants were 3387 MSM without a previous HIV diagnosis attending four HIV/STI diagnosis services in Madrid and Barcelona. Lifetime prevalence and prevalence ratios (PRs) by different factors were calculated using Poisson regression models with robust variance. We compared the characteristics of first drug injection episode, lifetime injection and risky injecting behaviors of those whose first injection was for sex (FIS) with those whose was not (non-FIS). Results Lifetime prevalence of injection was 2.1% (CI 1.7-2.7). In the multivariate analysis, it was strongly associated with having been penetrated by more than five men in the last 12 months (aPR = 10.4; CI 2.5-43.4) and having met most of their partners at private parties (aPR = 7.5; CI 4.5-12.3), and less strongly with other factors. Of those who had ever injected drugs, 81.9% injected for sex the first time they injected drugs (FIS). At first injection, FIS participants had a mean age of 31 years, 62.7% used mephedrone and 32.2% methamphetamine on that occasion. Of this FIS group 39.0% had ever shared drugs or equipment and 82.6% had always shared for sex. Some 30.8% of non-FIS reported having also injected drugs for sex later on. Conclusions Only two out of a hundred had ever injected, most to have sex and with frequent drug or injecting equipment sharing. Injecting for sex is the most common first episode of drug injection and is the most efficient risky behavior for the transmission of HIV, hepatitis B or C and other blood-borne infections. MSM participating in private parties should be considered a priority group for prevention policies.